Sobre predicativos condicionales, predicados estativos y cuestiones conexas - María Antonia Martínez Linares (Estudios de Lingüística, 2003)
Firstly, this paper deals with the diversity and complexity of secondary predicates. Secondly, it deals with stage-level secondary predicates with conditional content. The paper focuses on two aspects of these elements: certain properties of the main predicates related to conditional interpretation of secondary predicates, and the place of these elements in the sentence structure.